Spectroscopic detection of multiple populations in the ∼2 Gyr old cluster Hodge 6 in the LMC. Issue 4 (4th February 2019) - Hollyhead, K; Martocchia, S; Lardo, C; Bastian, N; Kacharov, N; Niederhofer, F; Cabrera-Ziri, I; Dalessandro, E; Mucciarelli, A; Salaris, M; Usher, C
Abstract: We report the spectroscopic discovery of abundance spreads (i.e. multiple populations) in the ∼2 Gyr old cluster in the LMC, Hodge 6. We use low-resolution VLT FORS2 spectra of 15 member stars in the cluster to measure their CN and CH band strengths at ≃3883 and 4300 Å, respectively, as well as [C/Fe] and [N/Fe] abundances. We find a subpopulation of two stars that are enriched in nitrogen, and we conclude that this subpopulation is evidence of multiple populations in Hodge 6. This is the second ∼2 Gyr old cluster (the first being NGC 1978 in the LMC) to show multiple populations and the first spectroscopic detection of MPs in a cluster of this age. This result is interesting as it hints at a possible relationship between the disappearance of extended main sequence turn-offs in clusters younger than ∼2 Gyr and the onset of multiple populations at ∼2 Gyr, which should be explored further.